ASSESSING ESG MATERIALITY THROUGH SUSTAINABILITY REPORT AND STAKEHOLDERS’ PERCEPTIONS - Dhevita Aufa Athary Vatsala; Tubagus Muhamad Yusuf Khudri (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2026)
This study aims to evaluate ESG materiality based on sustainability report disclosures and external stakeholder perceptions in a regional development bank. A qualitative case study approach was employed using content analysis and thematic analysis supported by NVivo software. The data were collected from the bank’s sustainability report, interviews, and questionnaires involving external stakeholders. The findings indicated that both the organization and stakeholders placed greater emphasis on social and governance issues than on environmental topics. Most ESG material topics showed relatively consistent priorities between the two perspectives, although differences remained for several topics. Overall, the findings suggest that the bank’s ESG disclosures generally reflect stakeholder priorities, while several areas require further strengthening to improve alignment with stakeholder expectations.